2008
DOI: 10.1038/sj.onc.1211000
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein induces the expression of MTA1 and HDAC1, which enhances hypoxia signaling in hepatocellular carcinoma cells

Abstract: Expression level of metastasis-associated protein 1 (MTA1) is closely related to tumor growth and metastasis in various cancers. Although increased expression level of MTA1 was observed in hepatocellular carcinoma (HCC), role of MTA1 complex containing histone deacetylase (HDAC) in hepatitis B virus (HBV)-associated hepatocarcinogenesis has not been studied. Here, we demonstrated that HBx strongly induced the expression of MTA1 and HDAC1 genes at transcription level. MTA1 and HDAC1/2 physically associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 48 publications
2
129
0
Order By: Relevance
“…MTA1 (metastatic tumor antigen 1), a component of nuclear remodeling histone deacetylate complex, is also modulated by HBx in liver cancer cells (26). MTA1 plays significant roles in both tumor biology and inflammation.…”
mentioning
confidence: 99%
“…MTA1 (metastatic tumor antigen 1), a component of nuclear remodeling histone deacetylate complex, is also modulated by HBx in liver cancer cells (26). MTA1 plays significant roles in both tumor biology and inflammation.…”
mentioning
confidence: 99%
“…Our laboratory, along with others, has shown that MTA1 associates with class I HDACs-HDAC1 and HDAC2 (28,32,33). However, MTA1 association with class II HDACs has not, as of yet, been documented.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 85%
“…Chang liver and Chang X-34, in which HBx gene expression is under the control of a doxycycline-inducible promoter, and SNU-354 were described previously. [22][23][24] HepG2 was obtained from the American Type Culture Collection. Cells were maintained in Dulbecco's modified Eagle's medium or Roswell Park Memorial Institute medium containing 10% fetal bovine serum at 37°C in a 5% CO 2 /95% air incubator.…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular fractionation, western blotting, immunoprecipitation, and immunocytochemistry were basically performed as previously described with specific antibodies against LXR␣ (Affinity BioReagents, Golden, CO), LXR␣, LXR␤, HBx, SREBP-1c, PPAR␣, PPAR␤, PPAR␥, stearoyl-coenyzme A desaturase-1 (SCD-1), hemagglutinin, ␤-actin (Santa Cruz Biotech-nology, Santa Cruz, CA), carbohydrate-responsive element-binding protein (ChREBP; Novus Biologicals, Littleton, CO), FLAG (Sigma, St. Louis, MO), or ␣-tubulin (Calbiochem, San Diego, CA). [22][23][24][25] Antibodies against FAS were kindly provided by Dr. K.-S. Kim at Yonsei University College of Medicine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation